The big aircraft carrier [videorecording (DVD)] - VanDerKloot, William (Big adventure series (Little Mammoth Media (Firm)), 2003)
See a giant aircraft carrier in action! Watch supersonic fighter jets take off and land! Discover how a carrier works, visit the control tower, bridge, kitchens, hangar deck, and more.